MgO nanoparticles obtained by Pulsed Laser Ablation in Liquid: a study on fabrication versatility aiming different applications - Pereira, Helena Filipa Ribeiro Silva (2022)
Apresentação efetuada em "Junior Euromat 2022", em Coimbra, 2022